FRAMEWORK OF ANALYZING THE CONDITIONS NECESSARY FOR IMPLEMENTING LAND CONSOLIDATION PROJECTS AT LOCAL LEVEL - LAURA CIOBANU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
The territorial distribution of land resources and the characteristics of rural organizational structures highlight different conditions for agricultural land consolidation. Knowing these conditions by identifying and correlating the favorable and restrictive factors reveals the feasibility of implementing consolidation projects at local level. The potential for consolidation in this paper takes into account the most important factors that influencing the implementation of consolidation projects in rural areas. The determination of these factors integrates aspects of competitiveness and the reduction of disparities in order to have a balanced development of rural areas and to ensure a real impact at the territorial level. The aim of this paper is to provide a conceptual model for estimating the potential for consolidation in rural areas in Romania by investigating the feasibility of implementing consolidation projects at the local level. The results consist in identifying the favorable conditions at the commune level that would facilitate the application of consolidation projects and the conditions specific to our country that highlight the main structural problems at the local level